2001
DOI: 10.1063/1.1342023
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration of eutectic SnPb solder interconnects for flip chip technology

Abstract: The electromigration of eutectic SnPb solder interconnects between a Si chip and a FR4 substrate was studied at 120 °C for up to 324 h with current stressing of 104 amp/cm2. Hillocks were observed at the anode and voids at the cathode. The dominant diffusing species was found to be Pb, confirmed by its accumulation at the anode. Diffusion markers were used to measure the electromigration flux and calculate the effective charge of atomic diffusion in the solder. Extensive microstructural evolution was also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(68 citation statements)
references
References 9 publications
4
64
0
Order By: Relevance
“…1,2) Following the size decrease of electrical packaging elements and an increase in usage efficiency, the electrical current in the unit area of the solders has been raised. For the current effect, a vacancy is induced by electromigration, the intermetallic compounds (IMC) grow unusually, [3][4][5] and the temperature is raised by the thermoelectric effect, 6) all of which may cause failure of the solders. Also, one related study 7) has revealed that the solders experience strain under a low current density.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Following the size decrease of electrical packaging elements and an increase in usage efficiency, the electrical current in the unit area of the solders has been raised. For the current effect, a vacancy is induced by electromigration, the intermetallic compounds (IMC) grow unusually, [3][4][5] and the temperature is raised by the thermoelectric effect, 6) all of which may cause failure of the solders. Also, one related study 7) has revealed that the solders experience strain under a low current density.…”
Section: Introductionmentioning
confidence: 99%
“…1 Under such a high current density, electromigration which can induce failure of solder joints is becoming a serious reliability issue in the microelectronics industry. 2 During electromigration, some damage, such as the formation of voids at the cathode and the growth of whiskers and hillocks at the anode, will occur in the solder or at the solder/underbump metallization (UBM) interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in-situ observation of the microstructural variation during the current stressing of the solder joints should be conducted to evaluate the effects of the two factors. The primary cause for current crowding is reported 15,16) to be the line-to-bump geometry of the solder bump joint, resulting in a higher current density in the solder regime than the average current density. However, the primary contributor for Joule heating in the solder joints is reported 15,16) to be the extremely thin and small dimension of Cu or Al traces on the Si chip.…”
Section: )mentioning
confidence: 99%
“…The primary cause for current crowding is reported 15,16) to be the line-to-bump geometry of the solder bump joint, resulting in a higher current density in the solder regime than the average current density. However, the primary contributor for Joule heating in the solder joints is reported 15,16) to be the extremely thin and small dimension of Cu or Al traces on the Si chip. Despite the different formation mechanisms of the two factors, the weak region for the electromigration of the solder should be near the entrance point of the Cu trace into the solder bump just beneath the passivation opening.…”
Section: )mentioning
confidence: 99%